MINIMALLY INVASIVE MANAGEMENT OF PARATHYROID ADENOMA: A CASE OF SUCCESSFUL THERMAL ABLATION IN A HIGH-RISK ELDERLY PATIENT - Tan, Ying-Jie; Eng, Shinye; Lim, Quan-Hziung; Hee, Nicholas Ken Yoong; Ooi, Ying-Guat; Khoo, Jun-Kit; Sarvanandan, Tharsini; Ratnasingam, J; Lim, Lee-Ling; Vethakkan, SR (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Primary hyperparathyroidism (PHPT) due to parathyroid adenoma often requires parathyroidectomy. However, surgery may not be feasible in high-risk patients. Thermal ablation techniques, such as microwave ablation (MWA), offer a minimally invasive alternative. We present a case of an elderly woman who was successfully treated with microwave ablation for severe hypercalcemia caused by a parathyroid adenoma. METHODOLOGY An 81-year-old semi-dependent female was diagnosed with parathyroid hormone (PTH)-dependent hypercalcemia in 2020 with a calcium level at 3.4 mmol/L (2.2–2.6) and an iPTH level at 69.7 pmol/L (1.96–8.49). Parathyroid ultrasound and 99m Tc MIBI parathyroid scintigraphy confirmed the presence of a right upper pole parathyroid adenoma, measuring 1.7 × 1.1 × 2.4 cm. Preoperative evaluation revealed an ectatic ascending thoracic aorta and aortic arch, causing tracheal deviation and restrictive lung disease, which placed her at high surgical risk. Initially, she was managed conservatively with cinacalcet 25–50 mg bd and denosumab 30–60 mg every 3–6 months. Unfortunately, her condition worsened despite intensified medical therapy, resulting in frequent hospitalizations due to severe hypercalcemia (calcium >3.5 mmol/L). Her iPTH levels increased to 204.7 pmol/L, and the adenoma grew to 2.1 × 1.9 × 3.1 cm. Given her deteriorating condition, she underwent ultrasound-guided microwave ablation of the adenoma. Two days after the procedure, her iPTH levels dropped by 80% to 11.3 pmol/L and stabilized between 35–40 pmol/L in the outpatient setting. Her post-procedural calcium level was within the mild hypocalcaemia range (2.8–3.0 mmol), and she no longer needed cinacalcet or pain medication. She experienced significant improvements in her physical function and could engage in static exercise. A follow-up ultrasound one month post-procedure revealed a 56% reduction in the adenoma’s volume. CONCLUSION Ultrasound-guided microwave ablation is an effective non-surgical treatment for PHPT in high-risk patients. It provides clinically significant improvements, reduces medication requirements, and enhances the quality of life.